1493 CD 64 as a Diagnostic Marker of a Serious Bacterial Infection in Children with Fever Presenting to the Emergency Department. (October 2012) - Veen, M van; Nijman, R; Zijlstra, M; Moll, H; Smit, F; Oostenbrink, R
Abstract : Background and Aims: Expression of neutrophile CD64 is elevated in presence of a bacterial infection. Studies on its diagnostic value show good results in adults, and diverse results in neonates and children admitted to the ICU with sepsis. We aimed to determine the diagnostic value of CD64 in children presenting with fever at the emergency department (ED), to detect a serious bacterial infection (SBI). Methods: We performed a prospective observational study including children aged 1 month-16 years with fever, who presented to the ED of a large teaching hospital in the Netherlands. Patients were excluded in case of relevant comorbidity. CD64 was determined using flowcytometry. SBI was assessed based on a combination of a positive culture, radiology or consensus diagnosis and included disease course follow up by an inpatient visit or telephonic follow up. Results: During 6 months in 2011 we included 208 children of whom CD64 was determined in 137 patients (66%). Preliminary results are based on 137 febrile children, of which 28 (20.4%) with a SBI. The area under the curve of the receiver operator curve to assess SBI was 0.65 (95% CI 0.53–0.77). Conclusion: In a sample of febrile children at the ED, we assessed moderate diagnostic value of CD64 as marker of a SBI. Our further analysis on complete sample (estimated n=280) will include diagnostic performance of CD64 for specific bacterial and viral diagnoses.